2017
DOI: 10.1177/1049732317745052
|View full text |Cite
|
Sign up to set email alerts
|

Mental Models of Cause and Inheritance for Type 2 Diabetes Among Unaffected Individuals Who Have a Positive Family History

Abstract: Using the familial risk perception (FRP) model as a framework, we elicited causal and inheritance explanations for type 2 diabetes (T2D) from people who do not have T2D but have a family history for it. We identified four composite mental models for cause of T2D: (a) purely genetic; (b) purely behavioral/environmental; (c) direct multifactorial, in which risk factors interact and over time directly lead to T2D; and (d) indirect multifactorial, in which risk factors interact and over time cause a precursor heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(38 citation statements)
references
References 32 publications
(60 reference statements)
0
35
0
Order By: Relevance
“…Those interested in participating contacted the research team, who then took them through the process of screening, consenting, and enrolling. Recruitment of individuals from the community‐based organization was completed through case workers, who passed on contact information to the research team (Daack‐Hirsch et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Those interested in participating contacted the research team, who then took them through the process of screening, consenting, and enrolling. Recruitment of individuals from the community‐based organization was completed through case workers, who passed on contact information to the research team (Daack‐Hirsch et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…We calculated age from birthdate and assigned values into one of two categories (a) under 35 years of age and (b) 35 years of age and older. We used a cutoff of 35 years old because participants indicated that risk for T2D is more of concern after the age of 35 (Daack‐Hirsch et al, ). Education was measured by asking for the highest level of education completed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we planned a mixed methods study to further develop the FRP model for people with a positive family history of T2D and are, themselves, unaffected. Previously, we described beliefs about cause, genetics and inheritance for T2D among participants in this study . In this article, we characterize salience and vulnerability.…”
Section: Introductionmentioning
confidence: 91%
“…To achieve diversity and ability to conduct the cluster analysis, our goal was to enrol 30 participants in each non‐Hispanic White, non‐Hispanic Black and Hispanic groups. Although individuals from other ethnic groups were not excluded, very few people from other ethnicities lived in the study's catchment area …”
Section: Qualitative Arm: the Frp Personalization Processmentioning
confidence: 99%